FAMILY COMMUNICATION AND WOMEN’S CREATIVE EMPOWERMENT IN YEHCANI VILLAGE, ABIANSEMAL BADUNG - Astuti Wijayanti; Shantika, Budi (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2025)
Family communication is a fundamental relational process that shapes emotional well-being, social learning, and individual creativity within households. This study explores how family communication contributes to women’s creative empowerment in Yeh Cani Village, Abiansemal, Badung. Previous research has emphasized mothers’ roles in maintaining family harmony; however, little attention has been given to how broader communication patterns within traditional communities foster women’s creativity. This research employed a qualitative descriptive design guided by Family Communication Patterns Theory and Symbolic Interactionism. Data were collected through in-depth interviews, participant observation, and document analysis involving eight women (aged 25–55) engaged in creative and productive activities. Data were analyzed using the Miles, Huberman, and Saldana (2014) interactive model. To ensure trustworthiness, member checking and triangulation of sources were conducted following Lincoln and Guba’s (1985) criteria for qualitative rigor. Findings reveal that open, dialogic communication fosters emotional support, collaboration, and creative initiative among women, whereas hierarchical, gendered communication limits self-expression. Women employ adaptive communication strategies, such as subtle persuasion and strategic timing grounded in Balinese values (rwa bhineda, tri hita karana) to maintain harmony while asserting creative agency. Nonverbal and emotional support (e.g. shared domestic labor and encouragement) emerge as a vital dimension of family interaction that reinforces empowerment. This study concludes that family communication in Balinese society operates as both a cultural system and a relational mechanism for empowerment. Open dialogue and empathetic interaction transform traditional family structures into spaces of creativity, equality, and resilience. By extending established communication theories into a Southeast Asian context, the findings contribute to theoretical understanding of family-based empowerment. Practically, they suggest that community-based gender programs should foster dialogic family communication (through empathy training, participatory dialogue, etc.) in alignment with Balinese local wisdom.